A Study on the Future Community Landscape Design Under the Background of COVID-19 - Xin, Yan; Yi, Jiao Zhou; Utaberta, Nangkula; Mohd Rasdi, Mohd Tajuddin (MAJ - Malaysia Architectural Journal, 2023)
This paper explores the methods of the innovative design of future community landscape design under the background of COVID-19. The concepts carry out the landscape design of community public facilities and contribute to communities and cities' safety and health. While enjoying the rapid changes in the urban living environment brought about by the modern industrial wave, we cannot ignore the aging of some communities in the city, which have become worthless spaces. The sustainable development of older communities has become a consideration for urban regeneration, with the landscape design of communities playing an active role in their revitalization. The community has played a vital role in preventing and controlling COVID-19 as a collection of populations. However, problems and deficiencies in community landscape design have also been identified. Based on the mode of operation of the community COVID-19, the community landscape design has been optimized in conjunction with the science and technology sector innovation.